Disperse Red 1 azo dye: Consequences of low-dose/low-concentration exposures in mice and zebrafish - Fernandes, Fábio Henrique [UNESP]; Abe, Flávia Renata; Gomes, Tamara Barbosa [UNESP]; Santos, Cibele Borges dos [UNESP]; Kempinas, Wilma De Grava [UNESP]; Leite, Bianca Arruda; de Oliveira, Danielle Palma; Salvadori, Daisy Maria Fávero [UNESP] (Elsevier, 2024)
Color Index Disperse Red 1 (DR1), an azo dye widely used in the textile industry and released into aquatic environments, is genotoxic in somatic cells, but little is known concerning its effects on the reproductive system or the early stages of embryonic development. We have assessed the effects on the spermatozoa of male mice following oral exposure to the dye, at low doses, for 14 days. Measured endpoints were DNA damage (comet assay), miRNA-34c levels, and sperm number, morphology, and motility. Exposure caused decreased miRNA-34c levels. We have also examined dye effects on zebrafish embryos and larvae, which included developmental impairment, altered glutathione transferase activity, and effects on reactive oxygen species and lipid peroxidation levels.
Keywords: Environmental pollutant; Germ cell; Sperm miRNA; Zebrafish Embryo development